SISTEM MONITORING PERKEMBANGAN ANAK BERBASIS DENVER DEVELOPMENT SCREENING TEST (DDST / DENVER II) - Rahadian Kurniawan; Izzati Muhimmah; Helmi Roichatul Jannah (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Even compared to the same age, the growth of every child is way different. The parent has to do an assessment against their child so that they could understand about how and how much the child grows. One of assessment methods that could be used is a Denver Development Screening Test (DDST) or usually called Denver II. Denver II contains 4 sectors which tested against children, those: Social Personal, Soft Motoric, Language, and Hard Motoric. An assessment using the Denver II could be conducted not only in the clinic or hospital but also in patient home using a help from a psychologist or other health workers as a tester. A DDST application based on Android was designed to facilitate a tester doing an assessment out of the clinic or hospital. Data of an assessment managed over a decision support system that build alongside a DDST application. Application was constructed based on instrument of Denver II, which are question form and manual test. Application testing conducted in two ways: usability testing, which could show whether an application could run well as the need lists; and validation testing using Single Decision Threshold have sensitivity amount of 100%, specificity amount of 87.5% and value apps performance amount of 90%. Using Coefficient Cohen’s Kappa has an accuracy amount of 0.74 (Strong).